Alexander, who's not (Do you hear me? I mean it!) going to move - Viorst, Judith; Preiss-Glasser, Robin (New York, N.Y. : Scholastic Inc., 1996)
Angry Alexander refuses to move away if it means having to leave his favorite friends and special places.
Large print.
Keywords: Moving, Household -- Fiction